An Examination of the Replica Journey in Travel Literature - Buckton-Tucker, Rosalind (2016)
The concept of the pilgrimage has given rise to a body of literature in which travellers record both the events of their journey with its underlying quest and their resulting spiritual and intellectual progress. Today, one form of pilgrimage is the replica journey retracing the paths of pilgrims and explorers from both ancient and more recent times. The resulting literature typically examines not only the authors’ own motivation and progress but also compares their journeys, both the physical and the emotional, to those of their predecessors, revisiting written accounts of the earlier ventures where they exist. This article will first discuss the concept of the pilgrimage, both religious and secular, and the urge to replicate well-documented travels, sometimes with contemporary equipment or dress, for the purpose of verifying physical facets of the journey or voyage or analyzing the characters who first undertook them. Next, the works of writers Tim Severin and Tim Mackintosh-Smith will be examined in the context of the above desire to recreate and record journeys that are challenging and enlightening both for the original travellers and their latter-day followers. Finally, the literary and cultural significance of their writing will be considered. Overall, the article will attempt to show how the ‘replica’ account adds a valuable diversity to existing travel literature and popular knowledge.